Relationship between macronutrient intake and growth pattern among orphan and non-orphan boys of Kolkata: a socio-physiological study - Roy, Pritha; Bandyopadhyay, Amit; Das, Moumita; Datta, Gouriprosad (International Journal Of Community Medicine And Public Health, 2025)
Background: Anthropometric data of orphan children are unavailable, especially in Indian context. It is also unaddressed that whether any difference in nutritional, physiological and socio-economic parameters exists between orphan and non-orphan children in our society. Methods: This cross-sectional study was conducted among 85 orphan boys from four different orphanages and 160 non-orphan boys from three different schools in Kolkata and surroundings. The body composition analysis and nutritional status was assessed by anthropometric measurements such as body height, body weight, BMI, skinfold measurements and dietary survey which was doing by using 24-hour dietary recall method. Statistical analysis was done by using SPSS software. Results: Orphan boys had significantly lower body weight, body height, and BMI compared to non-orphan boys. Higher prevalence of stunting (82.35%) and wasting (85.88%) among orphan boys were found. Lower body fat percentage and lean body mass in orphan boys were also found. Result showed significantly lower carbohydrate and fat consumption in orphan boys. Protein consumption was adequate in non-orphan boys but higher in orphan boys. Conclusions: Orphan boys in Kolkata are at risk of malnutrition, with lower anthropometric measurements and inadequate dietary intake. Comprehensive nutrition programmes are necessary to ensure the nutritional growth of children in orphanages.